DESAIN SISTEM INFORMASI ANGGARAN DENGAN ANALISIS RANTAI NILAI DALAM MENINGKATKAN EFISIENSI BIAYA PADA PERGURUAN TINGGI (STUDI KASUS POLITEKNIK NEGERI SEMARANG) - Azizah, Azizah - (Admisi dan Bisnis, 2014)
Traditional information systems budgets currently used in college still has some drawbacks. By using a value chain analysis which is the main building blocks of strategic cost management which lays out an analysis of the value chain that make up a product and services is expected to analyze the activities that can add value and activities that are not value-added to the college. Design of information systems based on the analysis of this activity will be instrumental in cost efficiency in the college because activities that have less value can be eliminated and give more portion to activities that add value.